Penerapan Metode Line Of Balance (LoB) pada Penjadwalan Proyek Perumahan - Sahadutha, Yeghal; Latupeirissa, Josefine Ernestine; Kusuma, Ari (Universitas Kristen Indonesia Paulus, 2025)
Scheduling in project implementation is very important to determine the work properly and correctly, therefore the construction of a project cannot be separated from scheduling in increasing project success. In houtilizing construction projects there is work that is done repeatedly or work with repetitive properties. The goal of this study is to compute the timing of the work of each unit of work. To get the outcomes of the timing of work in this study utilizing the Line of Balance (LoB) technique. This study is performed by field observation and calculating the timing of work from the volume value of each work unit. Based on the outcomes of the analysis performed for scheduling the project type 70/90 as many as 22 units, namely 1165 days or 3.2 years. This technique is effective because it displays production levels and time information in a graphical format so that it can figure out errors that happen.